Attraction of Trichogramma Wasps to Butterfly Oviposition-Induced Plant Volatiles Depends on Brassica Species, Wasp Strain and Leaf Necrosis - Afentoulis, Dimitrios G.; Cusumano, Antonino; Greenberg, Liana O.; Caarls, Lotte; Fatouros, Nina E. (Frontiers in Ecology and Evolution, 2021)
Within the Brassicaceae, wild as well as crop species are challenged by specialist herbivores including cabbage white butterflies (Pieris spp.). The wild crucifer Brassica nigra responds to oviposition by Pieris butterflies by the synergistic expression of two egg-killing traits. Genotypes that express a hypersensitive response (HR)-like necrosis (direct egg-killing) also emit oviposition-induced plant volatiles (OIPVs) attracting Trichogramma egg parasitoids (indirect egg-killing). This so-called double defence line can result in high butterfly egg mortalities. It remains unknown whether this strategy is unique to B. nigra or more common in Brassica species. To test this, we examined the response of different Trichogramma. evanescens lines to OIPVs emitted by B. nigra and three close relatives (B. napus, B. rapa and B. oleracea). Furthermore, we evaluated whether HR-like necrosis played a role in the attraction towards plant volatiles. Our results show a specificity in wasp attraction to different plant species. Three out of four plant species attracted a specific T. evanescens strain, including the crops B. rapa and B. napus. Parasitoid attraction was positively affected by presence of HR-like necrosis in one plant species. Our findings imply that, despite being a true generalist in terms of host range, T. evanescens shows intraspecific variation during host searching, which should be taken into account when selecting parasitoid lines for biocontrol of certain crops. Finally, we conclude that also crop plants within the Brassicaceae family possess egg-killing traits and can exert the double-defence line which may enable effective selection of egg-killing defence traits by cabbage breeders.